2017
DOI: 10.1515/opli-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Requests for Help in a Multilingual Professional Environment Testimonies and Actantial Models

Abstract: Professional multilingual environments using English as a lingua franca are prone to imbalances in communication, linguistic insecurity and rising tension. Non-native English speakers develop avoidance strategies in order to lessen their apprehension. To overcome these imbalances, this research aims to understand the relationships formed around languages focusing on the dynamics of integration and the requests for help. Guided by the actantial models of Greimas (1966), this qualitative study employs semiolingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…These statistical findings show no mediating effect from work experience on the participants' speaking and writing achievements. This echoes findings from other studies that found tailormade ESP module content that cater the learners' specific needs using authentic scenarios and tasks performed at workplace helped enhance their awareness of the range of structural and linguistic choices available in the professional settings in which they are actually made (Lejot, 2017;Zainuddin, Pillai, Dumanig & Phillip, (2019).…”
Section: Research Questionsupporting
confidence: 82%
“…These statistical findings show no mediating effect from work experience on the participants' speaking and writing achievements. This echoes findings from other studies that found tailormade ESP module content that cater the learners' specific needs using authentic scenarios and tasks performed at workplace helped enhance their awareness of the range of structural and linguistic choices available in the professional settings in which they are actually made (Lejot, 2017;Zainuddin, Pillai, Dumanig & Phillip, (2019).…”
Section: Research Questionsupporting
confidence: 82%